Somatic embryogenesis and plantlet regeneration from nucleus tissues of Local orange (Citrus sinensis (L.) Osbeck) - Huda Abdel-karim Al-TAHA; Abbas Mehdi JASIM; Muayed Fadhil ABBAS (Acta Agriculturae Slovenica)
Somatic embryogenesis and plantlet regeneration were achieved in callus cultures of nucellus tissues derived from undeveloped ovules of immature fruits of local orange (Citrus sinensis (L.) Osbeck). Four types of culture media were used and all produced embryogenic callus. Somatic embryos were developed on MS medium supplemented with BA only. Embryo maturation took place on MS medium supplemented with BA and 2,4-D. Plantlets were regenerated from those somatic embryos on half strength MS medium free of plant growth regulators. The well-developed plantlets were transferred to a potting mix containing sand and peat moss (2: 1) and grown for 8 months, with a survival rate of 100 %.